Economic reforms and poverty alleviation in India / edited by C. H. Hanumantha Rao and Hans Linnemann - "Linnemann, Hans (ed.)" (New Delhi, 1998)
Following a severe balance of payments crisis, India launched a series of economic reforms in 1991. The essays in this volume present the latest information on the stabilization and structural adjustment measures introduced in India and their impact upon the balance of payments, growth, employment, inflation and poverty. In the light of data from these areas, the contributors examine issues including: differentials in urban and rural poverty; whether the rise in the incidence of poverty is an inevitable consequence of the reform process; and the role the state can play in the new order.
Keywords: India economic policy 1947